PENGAMANAN DOKUMEN KEPEGAWAIAN PADA DINAS PENDIDIKAN TEMANGGUNG DENGAN ALGORITMA RC4 DAN AES-256 - Pratama, Fathur Setya; Romli, Moh Ali (Yayasan Pendidikan Cahaya Budaya Indonesia, 2024)
The Education, Youth and Sports Office of Temanggung Regency is a government agency responsible for the education, culture and sports sectors in Temanggung Regency. Currently, personnel documents in this institution are still stored without certain access restrictions. This condition provides an opportunity for unauthorized individuals to access these personnel documents. Lack of data protection has the potential to pose a risk of data leakage and manipulation. Therefore, research was conducted involving the use of the RC4 cryptographic method combined with the AES-256 method to improve the security of personnel documents. The documents will be encrypted using the RC4 method, where the values will undergo permutation before being further encrypted using the AES-256 method. This encryption process involves four types of byte conversion, namely SubBytes, ShiftRows, MixColumns, and AddROUNDKey. The test results show that the encryption applied successfully functions properly, so that individuals who do not have the encryption key cannot access the document. Thus, the security of personnel documents can be improved, and unauthorized access can be prevented.